E-174 Severity of vasospasm associated with development of collaterals following aneurysmal subarachnoid hemorrhage. (22nd July 2018) - Al-Mufti, F; Manning, N; Crimmins, M; Amuluru, K; Majmundar, N; El-Ghanem, M; Patel, V; Agarwal, S; Park, S; Willey, J; Kamel, H; Connolly, S; et al.
Abstract : Introduction: Cerebral collateral circulation has been studied extensively in ischemic stroke where it has been shown to be a predictor of reperfusion, final infarct size, and outcome. Little is known about the significance of the collaterals in the setting of aneurysmal subarachnoid hemorrhage (aSAH). We sought to evaluate the effect of cerebral vasospasm on the development of cerebral collaterals following aneurysmal subarachnoid hemorrhage and the effects of the later on delayed cerebral ischemia (DCI). Methods: We retrospectively evaluated 64 aSAH patients with evidence of DCI between day 5 and 7, enrolled in a prospectively maintained observational cohort study. Angiograms were evaluated by 4 blinded neurointerventionalists. We compared good collateral grades to poor collateral grades, additionally we compared enrolled individuals with any collaterals versus patients who had no collaterals. Results: Inter-rater reliability for collateral grades was substantial (weighted kappa 0.632). Mild vasospasm was more frequent in patients with poor collateral grades compared to patients with good collateral grades (32% vs 4% p=0.012). There was no difference between the collateral groups with regards to DCI, functional or cognitive outcome. Patients adjudicated to have any collaterals were more likely to have severe vasospasm (62% vs 33% p=0.023) and less likely to have mild vasospasm (37% vs 9% p=0.007). In a multivariable model, vasospasm severity remained associated with collateral status, while aneurysm location was not. Conclusions: The severity of vasospasm following aSAH was associated with the development of collaterals. There was no difference between collateral grades with regards to DCI or outcome. Disclosures: F. Al-Mufti: None. N. Manning: None. M. Crimmins: None. K. Amuluru: None. N. Majmundar: None. M. El-Ghanem: None. V. Patel: None. S. Agarwal: None. S. Park: None. J. Willey: None. H. Kamel: None. S. Connolly: None. P. Meyers: None. J. Claassen: None.